A Lagrangian study tracing water parcel origins in the Canary Upwelling System - Mason, Evan; Colas, Francois; Pelegrí, Josep L. (Scientia Marina, 2012)
The regional ocean circulation within the Canary Upwelling System between 31°N and 35°N is studied using numerical tools. Seasonal mean and near-instantaneous velocity fields from a previously-generated climatological Regional Ocean Modelling System (ROMS) solution of the Canary Basin are used to force a series of offline Lagrangian particle-tracking experiments. The primary objective is to identify the pathways through which water parcels arrive at the upwelling region north of Cape Ghir. Examining year-long pathways, the Azores Current contributes over 80% of particles annually, of which a large proportion arrive directly from offshore (from the northwest), while others travel along the shelf and slope from the Gulf of Cadiz. The remaining 20% originate within the Gulf of Cadiz or come from the south, although the southern contribution is only significant in autumn and winter. When season-long pathways are considered, the alongshore contributions become increasingly important: northern contributions reach 40% in spring and summer, while southern values exceed 35% in winter. This study also shows that coastal upwelling changes both spatially and temporally. Upwelling becomes intensified near Cape Beddouza, with most upwelling occurring within 40 km from shore although significant values may reach as far as 120 km offshore north of Cape Beddouza; at these locations the offshore integrated upwelling reaches as much as 4 times the offshore Ekman transport. In the Cape Beddouza area (32°N to 33°N), upwelling is negligible in February but intensifies in autumn, reaching as much as 3 times the offshore Ekman transport.